1997
DOI: 10.1111/1468-5884.00053
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Object Unity in a Chimpanzee (Pan troglodytes)

Abstract: Identifying objects is one of the most important agendas for animals in their daily lives. Quick and correct identification of foods or predators decreases risks to their lives. However, in the natural environment, objects are not always fully visible: They are often occluded by other objects and only partly visible. Therefore the ability to complete invisible parts of objects is an essential aspect of perceptual or cognitive processes. Nevertheless, this kind of perceptual completion has not been investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
53
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 14 publications
5
53
0
1
Order By: Relevance
“…Watanabe & Cavanagh, 1993). Several studies in nonhuman primates have also investigated the role of junctions (T, L, or X) in the perception of object overlap, revealing that monkeys and apes perceive the occlusion or transparency of two-dimensionally displayed objects using the clues of the junctions (e.g., Fujita & Giersch, 2005;Nagasaka, Nakata, & Osada, 2009;Sato, Kanazawa, & Fujita, 1997;Sugita, 1999). Our results, which demonstrate that the addition of X-junctions promoted streaming percepts, are consistent with the results of these studies.…”
Section: Discussionsupporting
confidence: 91%
“…Watanabe & Cavanagh, 1993). Several studies in nonhuman primates have also investigated the role of junctions (T, L, or X) in the perception of object overlap, revealing that monkeys and apes perceive the occlusion or transparency of two-dimensionally displayed objects using the clues of the junctions (e.g., Fujita & Giersch, 2005;Nagasaka, Nakata, & Osada, 2009;Sato, Kanazawa, & Fujita, 1997;Sugita, 1999). Our results, which demonstrate that the addition of X-junctions promoted streaming percepts, are consistent with the results of these studies.…”
Section: Discussionsupporting
confidence: 91%
“…In adults and older infants, such perception of object unity occurs in the absence of common motion, when two static rods are merely aligned to make good continuity. Sato, Kanazawa, and Fujita (1997) recently demonstrated that an adult chimpanzee showed similar perception. They trained the subject on a matching-to-sample of one rod and two rods.…”
mentioning
confidence: 98%
“…Through amodal completion, an animal can perceive a figure as a whole even if another object conceals a portion of it (Michotte, Thines, & Crabbe, 1964). Mammals (Kanizsa, Renzi, Conte, Compostela, & Guerani, 1993;Sato, Kanazawa, & Fujita, 1997), birds (Regolin & Vallortigara, 1995), fish (Sovrano & Bisazza, 2008) and even invertebrates (van Hateren et al, 1990;Zylinski, Darmaillacq, & Shashar, 2012) use this mechanism just as humans do (Kanizsa, 1979).…”
mentioning
confidence: 99%